Análise das necessidades em saúde dos sujeitos em situação de rua, atendidos em um hospital público no município de São Paulo - Pereira, Andiara Lucia Cardoso Magalhães [UNIFESP] (2018)
This assigment searched to investigate, analyze and describe how the patients of the Municipal Hospital Dr. Arthur Ribeiro de Saboya (located in the southern region of the city of São Paulo) are organized after hospital discharge, convalescent subjects in the street situation. The Decree No. 7.053 which established the National Policy for Social Inclusion of Population in the Street Situation (PNISPSR), provides for access to intersectoral network resources, guaranteeing the rights of this population. Therefore, the first chapter of this study presents a retrospective of the advances made from the Federal Constitution of 1988 with a Social Security Policy approach, guaranteeing the Universal Right to Health and Social Assistance to those who need it, as well as PNISPSR and the current situation. The second chapter dealt with conceptual categories relevant to health work such as rights, poverty, among others related to the theme in order to base the place of these subjects in society. And finally in the third chapter analyzed data from primary sources derived from semi-structured interviews conducted with users in this situation that were duly socialized from the findings. In addition to the profile of the subjects, the narratives of these subjects' difficulties in accessing rights in relation to the intersectoral network and their anguish in the face of scarce resources and the absence of the State through social politics that do not effectively guarantee social protection to the population in question. Finally important considerations and recommendations for the continuity of studies and deepening of the thematic.